Clinical Significance of Pain at Hospital Discharge Following Traumatic Orthopedic Injury: General Health, Depression, and PTSD Outcomes at 1 Year. Issue 3 (March 2016) - Archer, Kristin R.; Heins, Sara E.; Abraham, Christine M.; Obremskey, William T.; Wegener, Stephen T.; Castillo, Renan C.
Abstract : Objectives: The purpose of this study was to determine whether pain at hospital discharge is associated with general health and depression and posttraumatic stress disorder (PTSD) at 1 year following traumatic orthopedic injury. Materials and Methods: This study prospectively enrolled 213 patients, 19 to 86 years of age, admitted to an academic level 1 trauma center for surgical treatment of a traumatic lower-extremity or upper-extremity orthopedic injury. Pain at hospital discharge was measured with the Brief Pain Inventory. At 1-year follow-up, physical and mental health was assessed with the SF-12 and depressive and PTSD symptoms with the 9-item Patient Health Questionnaire (PHQ-9) and PTSD Checklist-Civilian Version (PCL-C), respectively. Cut-off scores of 10 on the PHQ-9 and 44 on the PCL-C classified patients as having depression or PTSD. Results: A total of 133 patients (62%) completed follow-up at 1 year. Responders and nonresponders did not differ significantly on baseline characteristics. Multivariable regression found that increased pain at discharge was significantly associated with depression (odds ratio=3.3; P <0.001) and PTSD (odds ratio=1.4; P =0.03) at 1 year, after controlling for age, education, injury severity score, and either depressive or PTSD symptoms at hospital discharge. Early postoperative pain was not a significant risk factor for long-term physical and mental health. Discussion: Findings highlight the importance of early screening for uncontrolled postoperative pain to identify patients at high risk for poor psychological outcomes and who could benefit from more aggressive pain management. Results suggest early interventions are needed to address pain severity in patients with orthopedic trauma.